Conservação de goiabas ‘Pedro Sato’ minimamente processadas e irradiadas - Campos, André José de; Fujita, Erika; Morais, Maria Rosa de [UNESP]; Neves, Leandro Timoni; Vieites, Rogério Lopes [UNESP]; Chagas, Edvan Alves (Universidade Federal de Roraima, 2011)
The aim of this study was to evaluate the effect of gamma irradiation associated with modified atmosphere in cold storage of guava ‘Pedro Sato’ minimally processed, checking their physical-chemical characteristics. Were used guavas from the region of Vista Alegre do Alto/São Paulo/Brazil. After harvest, fruits were immediately transported to the Fruit and Vegetables Laboratory from the Agroindustrial Management and Technology Department, Agronomic Sciences College - UNESP - Botucatu / SP, where they were kept at 10 ° C and 90-95% RH in cold storage, for 12 days. In the laboratory, fruits were selected by size and lack of defects in order to standardize the lot and then were cut into slices 0.5 cm thick. We used the completely randomized design, with factorial design 5 x 5, with three replications. The first factor consisted of the following effects: control 1 (without package or irradiation), control 2 (polystyrene package/PS + package low density polyethylene/LDPE and without irradiation), treatment 1 (PS + LDPE and 0.2 kGy ), treatment 2 (PS + LDPE and 0.6 kGy) and treatment 3 (PS + LDPE and 1.0 kGy). The second factor consisted of the evaluation periods: 0, 3, 6, 9 and 12 days. The analyses were: firmness, soluble solids (SS), titratable acidity (TA), maturity index, pH, breathing behavior. In the end of this work it was concluded that the lower dose of radiation associated with modified atmosphere promoted positive effect on physical-chemical characteristics of guava ‘Pedro Sato’, providing fruits with higher quality and durability, due to higher maintenance of pulp firmness, the highest pH and soluble solids obtained. Regarding the storage days, there were no beneficial effect of the treatments during storage, mainly due to the sensitivity of fruits submitted to gamma irradiation, where only the early days provided better values for the variables.

O objetivo desse trabalho foi avaliar o efeito da irradiação gama associada à atmosfera modificada passiva na conservação refrigerada de goiabas ‘Pedro Sato’ minimamente processadas. Foram utilizadas goiabas provenientes da região de Vista Alegre do Alto/São Paulo/Brasil. Após a colheita, as goiabas foram imediatamente transportadas ao Laboratório de Frutas e Hortaliças, pertencente ao Departamento de Gestão e Tecnologia Agroindustrial, da Faculdade de Ciências Agronômicas – UNESP – Campus de Botucatu/SP, onde foram mantidas a 10ºC e 90-95%UR em câmara frigorífica, por 12 dias. No laboratório, as goiabas foram selecionadas quanto ao tamanho e ausência de defeitos, visando uniformizar o lote e, posteriormente foram cortadas em fatias com 0,5 cm de espessura. Foi utilizado o delineamento inteiramente aleatorizado, com esquema fatorial 5 x 5, com três repetições. O primeiro fator consistiu dos seguintes efeitos: controle 1 (sem embalagem e sem irradiação); controle 2 (embalagem de poliestireno/PS + embalagem de polietileno de baixa densidade/PEBD e sem irradiação); tratamento 1 (PS+PEBD e 0,2kGy); tratamento 2 (PS+PEBD e 0,6kGy) e tratamento 3 (PS+PEBD e 1,0kGy).O segundo fator consistiu dos períodos de avaliação, sendo: 0, 3, 6, 9 e 12 dias. As análises realizadas foram:firmeza, sólidos solúveis (SS), acidez titulável (AT), índice de maturação, pH, taxa de respiração. Concluiu-se que a menor dose de irradiação associada a atmosfera modificada passiva promoveu efeito positivo nas características físico-químicas da goiaba ‘Pedro Sato’, proporcionando frutos com maior durabilidade e qualidade, devido a maior manutenção da firmeza de polpa e aos mais elevados valores de pH e sólidos solúveis obtidos. Em relação aos dias de armazenamento, não foi verificado efeito benéfico dos tratamentos no decorrer do armazenamento, principalmente devido à sensibilidade dos frutos submetidos à irradiação gama, onde somente os dias iniciais promoveram os melhores valores para as variáveis estudadas.
Conservation guavas ‘Pedro Sato’ minimally processed and irradiated
Keywords: Psidium guajava L; Doses; Gases; Minimal processing; Psidium guajava L; Doses; Gases; Processamento mínimo